MicroRNA: trends in clinical trials of cancer diagnosis and therapy strategies - Kim, Taewan; Croce, Carlo M. (Experimental & molecular medicine, 2023)
As a type of short noncoding RNAs, microRNA (miRNA) undoubtedly plays a crucial role in cancer development. Since the discovery of the identity and clinical functions of miRNAs, over the past few decades, the roles of miRNAs in cancer have been actively investigated. Numerous pieces of evidence indicate that miRNAs are pivotal factors in most types of cancer. Recent cancer research focused on miRNAs has identified and characterized a large cohort of miRNAs commonly dysregulated in cancer or exclusively dysregulated in specific types of cancer. These studies have suggested the potential of miRNAs as biomarkers in the diagnosis and prognostication of cancer. Moreover, many of these miRNAs have oncogenic or tumor-suppressive functions. MiRNAs have been the focus of research given their potential clinical applications as therapeutic targets. Currently, various oncology clinical trials using miRNAs in screening, diagnosis, and drug testing are underway. Although clinical trials studying miRNAs in various diseases have been reviewed before, there have been fewer clinical trials related to miRNAs in cancer. Furthermore, updated results of recent preclinical studies and clinical trials of miRNA biomarkers and drugs in cancer are needed. Therefore, this review aims to provide up-to-date information on miRNAs as biomarkers and cancer drugs in clinical trials. Cancer: Clinical trials on microRNAs’ diagnostic and therapeutic potential The discovery of microRNAs' critical role in tumor development has sparked numerous clinical trials focused on evaluating their potential as biomarkers and targets for anti-cancer therapies. Taewan Kim from Shenzhen University, China, and Carlo Croce from The Ohio State University in Columbus, USA, summarize the various ongoing and completed trials aimed at determining whether cancer-linked microRNAs found in blood or tissues can serve as accurate predictors of cancer development or drug efficacy. The researchers discuss the development of drug mimics or inhibitors of specific microRNAs that are now in or nearing human testing as potential anti-cancer therapeutics. Although the research is still in its early stages, the authors envision a future where microRNA-based medicines and diagnostics become routine in cancer patient care, improving personalized treatment strategies and outcomes.